Malawi: The impact of COVID-19 and food system responses - COVID-19 Hub (International Food Policy Research Institute, 2021)
Malawi, like other southern African countries, has endured several waves of infection since the COVID-19 pandemic started. The disease has had severe effects on the economy, including the agriculture sector. CGIAR and partners have been working in the country to determine the economic impacts, improve seed systems, and implement climate-smart technologies on farms.